1998
DOI: 10.1159/000017847
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Antibiotics for Acne

Abstract: Antibiotic therapy for acne is very common. Antibiotics are frequently used in acne, either systemically or topically. Systemic antibiotics are indicated as treatment of moderate and quite severe acne or if acne is considered as very serious by the patient for psychological or social reasons. Results are very often excellent, but failure is possible; in this case using another treatment, especially isotretinoin, is necessary. A few antibiotics are useful: tetracyclines (tetracycline, doxycycline, minocycline, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
8

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 50 publications
0
31
0
8
Order By: Relevance
“…For the antibiotic therapy, tetracycline, erythromycin, and lincomycin are generally used in the treatment [6,7]. With the increasing of antibiotic application, the increased prevalence of the antibiotic resistant bacteria has been reported [24]. Also, it has been previously reported on the antibiotic resistance of acne-related bacteria.…”
Section: Antibiotic Resistance Of Acne-related Bacteria Against Commementioning
confidence: 99%
“…For the antibiotic therapy, tetracycline, erythromycin, and lincomycin are generally used in the treatment [6,7]. With the increasing of antibiotic application, the increased prevalence of the antibiotic resistant bacteria has been reported [24]. Also, it has been previously reported on the antibiotic resistance of acne-related bacteria.…”
Section: Antibiotic Resistance Of Acne-related Bacteria Against Commementioning
confidence: 99%
“…Similarly, Jatoi et al analysed the effect of an oral tetracycline prophylaxis on the development of skin exanthemas of a grade greater than or equal to 2, and found that prophylaxis with tetracycline was effective during the first weeks, but ineffective in a longterm setting (9). These antibiotics are commonly used for the treatment of acne, and the clinical similarity between classical acne and an eGFr inhibitor-induced skin exanthema suggests that this antibiotic may play a role in preventing or treating drug-induced exanthemas (10,11). however, tetra-/doxy-/ and minocycline carry anti-inflammatory effects that may also support exanthema palliation (11,12).…”
Section: Cetuximab-induced Skin Exanthema: Improvement By a Reactive mentioning
confidence: 99%
“…These antibiotics are commonly used for the treatment of acne, and the clinical similarity between classical acne and an eGFr inhibitor-induced skin exanthema suggests that this antibiotic may play a role in preventing or treating drug-induced exanthemas (10,11). however, tetra-/doxy-/ and minocycline carry anti-inflammatory effects that may also support exanthema palliation (11,12).…”
Section: Cetuximab-induced Skin Exanthema: Improvement By a Reactive mentioning
confidence: 99%
“…A number of further drugs can also secondarily induce keratolysis over their influence on other pathogenic factors [31]. Benzoyl peroxide and topical and systemic antibiotics primarily exhibit antimicrobial, but also anti-inflammatory activities [32, 33]. Various agents administered in acne treatment exhibit direct or indirect anti-inflammatory activities in addition to their effects on further pathogenic factors of acne.…”
Section: Therapeutic Targets and Acne Drugsmentioning
confidence: 99%
“…Oral antibiotics are indicated for several groups of patients with inflammatory acne (table 3) [33, 38]. They include tetracyclines (tetracyclines, doxycycline, minocycline), erythromycin, clindamycin, and cotrimoxazole (table 4).…”
Section: Systemic Treatmentmentioning
confidence: 99%